Blockchain networks as constitutional and competitive polycentric orders. Issue 5 (10th October 2022) - Alston, Eric; Law, Wilson; Murtazashvili, Ilia; Weiss, Martin
Abstract: Institutional economists have analyzed permissionless blockchains as a novel institutional building block for voluntary economic exchange and distributed governance, with their unique protocol features such as automated contract execution, high levels of network and process transparency, and uniquely distributed governance. But such institutional analysis needs to be complemented by polycentric analysis of how blockchains change. We characterize such change as resulting from internal sources and external sources. Internal sources include constitutional (protocol) design and collective-choice processes for updating protocols, which help coordinate network participants and users. External sources include competitive pressure from other cryptocurrency networks. By studying two leading networks, Bitcoin and Ethereum, we illustrate how conceptualizing blockchains as competing and constitutional polycentric enterprises clarifies their processes of change.